Permian-Triassic maturation and multistage migration of hydrocarbons in the Assistência Formation (Irati Subgroup), Paraná Basin, Brazil: implications for the exploration model - A., Mateus (2014)
New lines of geological evidence strongly suggest that the main period of hydrocarbon maturation within Assistência Formation should be Permian-Triassic, stimulated by a high geothermal gradient that also sustained various manifestations of hydrothermal activity. Three main stages of fluid/hydrocarbon migration can also be inferred on the basis of multiscale observations: confined flow in late Permian to Triassic times, depending on the local build-up of fluid pressures; heterogeneous flow in Lower Cretaceous, triggered by a rejuvenated temperature gradient assisted by the early developed permeability conditions; and a late flow possibly driven by local pressure gradients, after complete cooling of dolerite dykes/sills. The early maturation and multistage migration of hydrocarbons have significant consequences in the design of exploration models to be applied in Paraná Basin.